2020
DOI: 10.17392/1175-20
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with overweight and obesity in preschool children

Abstract: <p><strong>Aim<br /></strong> To determine factors associated with overweight/obesity in preschool children. <br /><strong>Methods<br /></strong> This cross-sectional study was carried out in paediatric outpatient departments of the Public Institution Primary Health Care Centre of Canton Sarajevo, Bosnia and Herzegovina. The study included 300 preschool children who were divided into two groups: norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Previous research has shown a correlation between high levels of physical activity and lower rates of overweight and obesity in children [ 41 ]. This study, however, observes changes in zBFP among overweight children in relation to their 24-hour activity patterns, particularly noting variations associated with engaging in MVPA for more than 30 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown a correlation between high levels of physical activity and lower rates of overweight and obesity in children [ 41 ]. This study, however, observes changes in zBFP among overweight children in relation to their 24-hour activity patterns, particularly noting variations associated with engaging in MVPA for more than 30 minutes.…”
Section: Discussionmentioning
confidence: 99%
“… 4 In this sense, the percentage of obesity increases from 8% to 35% when the sedentary behavior measured by screen time is greater than 180 min a day. 5 …”
Section: Introductionmentioning
confidence: 99%